A New Grease-Pocket Shape to Extend the Service Life of Grease - Sumiko Hibino (Japanese Society of Tribologists, 2008)
The peroidicity of motor disassembly for maintenance is currently determined by the durability of the sealed grease they contain. The lifetime of this grease is the shortest of all the motor's bearing parts and materials, and therefore needs to be made longer. For this purpose, therefore, the authors discussed the shape of the grease pocket, and concluded that the efficiency of lubrication depends on the shape of the pocket and the relative position between pockets and the bearing, which should be appropriately modified. In this report, the authors performed laboratory testing with full-scale grease pocket models of refined and conventional shapes to compare the service lives and determine the effects of improvement.